Status Gizi Remaja Sekolah Menengah Atas/Sederajat Umur 13 – 18 Tahun di Kota Sibolga - Bibi Ahmad Chahyanto; Yayuk Susilo (Kabar Gizi Indonesia, 2025)
Adolescence is a unique period of the life cycle and is vulnerable to nutritional problems, thus regular monitoring of nutritional status is crucial to be done. This study aims to describe the nutritional status of adolescent high school students aged 13-18 years in Sibolga City. This descriptive research employing a cross-sectional study design used secondary data from the health screening results of new students in class XI SMA / equivalent in the 2018/2019 academic year in Sibolga City. Further data processing and analysis were carried out from January to July 2023. The number of data that met the research inclusion criteria and were further processed was 1.443 respondents. Univariate analysis was used to describe the description of the frequency and percentage values of each variable. The study proved that most respondents were 13-15 years old (80.87%) and attended public schools (64.17%). The proportion of female gender was 62.86% more than male (37.24%). Most respondents had good nutritional status (74.57%). The prevalence of respondents with poor nutritional status was 0.97%, undernutrition 5.40%, overnutrition 15.11%, and obesity 3.95%. The nutritional status of adolescent high school students aged 13-18 years in Sibolga City is quite good, but nutritional problems, such as malnutrition, undernutrition, overnutrition, and obesity are still found. Therefore, they need to be aware and addressed as they can affect nutritional status and health and productivity in adolescence and in the future.